Effect of Supply Chain Management: Just in Time for Competitiveness and Corporate Performance in Industrial Area Manufacturing Company in Makassar - Fajriah, Yana; Themba, Orfyanny S; ., Pattarapanna (Information Management and Business Review, 2016)
This research design using survey method with data collection in cross-section through a questionnaire. The samples using simple random sampling with the number of respondents is 132 Managers in Manufacturing Company in Makassar Industrial Area. Data analysis method used in testing the hypothesis was Structural Equation Modeling (SEM). The results of the study provide evidence that just in time has no significant effect on the performance of the company. Supply chain management and competitive advantage have significant influence on the performance of the company. Supply chain management has significant influence on the competitive advantage. Competitive Advantage is a complete mediation in describing just in time for the performance of the company while in explaining the effect of supply chain management on the performance of the company, acting as a competitive advantage partial mediation. The practical implications of this research may provide an improved understanding of managers in improving company performance through competitive advantages influenced by supply chain management and just-in-time. Limitations of this study on a sample size of only using the manager just limiting the generalization the research finding. Originality of this study provide a basis for the development configuration modeling using SEM and conceptual models that prove the influence of supply chain management and just-in-time to the improvement of the performance of the company by entering a competitive advantage as mediation relationships between variables, which in previous studies carried out separately.